2020
DOI: 10.1049/iet-epa.2019.0547
|View full text |Cite
|
Sign up to set email alerts
|

Rotor eddy current analysis and optimisation design of intermediate ring in novel double squirrel‐cage induction motor

Abstract: The intermediate ring (IR) in the novel squirrel-cage rotor is vulnerable to electrical faults for its relatively small dimension. With the investigation of IR current features, this study mainly proposes an optimisation design strategy of IR to avoid excessive thermal stress at a start-up instant. The amplitude and phase relations of various rotor currents are reflected in the proposed current phasor diagram. In terms of the internal distribution of one concrete current, the circuit analysis theory is applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…It can be concluded that increasing the axial length of the intermediate ring will not lead to more improved results. In segmented rotor structures with intermediate rings, the axial length is usually selected 1 or 2% of the stack length for optimum performance (Xu et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that increasing the axial length of the intermediate ring will not lead to more improved results. In segmented rotor structures with intermediate rings, the axial length is usually selected 1 or 2% of the stack length for optimum performance (Xu et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…By ignoring the magnetic nonlinearity, the stator and rotor MMFs (which contribute to the magnetic field in the air gap) can be separated from each other, assuming that the first is fixed while the second rotates according to the virtual rotor displacement (Pyrhönen et al , 2008). Besides, as mentioned in (Xu et al , 2020), the air gap flux density can be decomposed into fundamental and harmonic components. However, in the case of the fundamental toque-producing air gap flux density, the situation does not vary notably from no-load to the rated torque in most IMs, as experience shows (Boldea and Nasar, 2018).…”
Section: Design Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The internal shape of the rotor bars and their overall arrangement can also be very varied, e.g., single straight bars, skewed bars, and single or double cage rotors. The shape of arrowed rotor bars with a middle ring is also often found [10,11]. The rotor slots can be open, semi-closed, or fully closed [12][13][14].…”
Section: Introductionmentioning
confidence: 99%